Thermally-induced softening of PNIPAm-based nanopillar arrays. Issue 13 (13th March 2017) - Sanz, Belén; von Bilderling, Catalina; Tuninetti, Jimena S.; Pietrasanta, Lía; Mijangos, Carmen; Longo, Gabriel S.; Azzaroni, Omar; Giussi, Juan M.
Abstract : We prepared poly( N -isopropylacrylamide)-based nanopillars that, contrary to expectations, showed a thermally-induced softening above the lower critical solution temperature. Abstract : The surface properties of soft nanostructured hydrogels are crucial in the design of responsive materials that can be used as platforms to create adaptive devices. The lower critical solution temperature (LCST) of thermo-responsive hydrogels such as poly( N -isopropylacrylamide) (PNIPAm) can be modified by introducing a hydrophilic monomer to create a wide range of thermo-responsive micro-/nano-structures in a large temperature range. Using surface initiation atom-transfer radical polymerization in synthesized anodized aluminum oxide templates, we designed, fabricated, and characterized thermo-responsive nanopillars based on PNIPAm hydrogels with tunable mechanical properties by incorporating acrylamide monomers (AAm). In addition to their LCST, the incorporation of a hydrophilic entity in the nanopillars based on PNIPAm has abruptly changed the topological and mechanical properties of our system. To gain an insight into the mechanical properties of the nanostructure, its hydrophilic/hydrophobic behavior and topological characteristics, atomic force microscopy, molecular dynamics simulations and water contact angle studies were combined. When changing the nanopillar composition, a significant and opposite variation was observed in their mechanical properties. As temperature increased above the LCST, the stiffness of PNIPAm nanopillars, as expected, did so too, in contrast to the stiffness of PNIPAm–AAm nanopillars that decreased significantly. The molecular dynamics simulations proposed a local molecular rearrangement in our nanosystems at the LCST. The local aggregation of NIPAm segments near the center of the nanopillars displaced the hydrophilic AAm units towards the surface of the structure leading to contact with the aqueous environment. This behavior was confirmed via contact angle measurements below and above the LCST.